2006
DOI: 10.1530/eje.1.02281
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonist therapy of clinically non-functioning pituitary macroadenomas. Is there a role for 123I-epidepride dopamine D2 receptor imaging?

Abstract: Objective: Clinically non-functioning pituitary adenomas (NFPAs) can express functional dopamine D2 receptors. Therapy with dopamine (DA) agonists may result in a NFPA size reduction. However, DA agonist-sensitive and -resistant NFPAs are clinically indistinguishable. We have studied the correlation between in vivo imaging of D2 receptors using 123 I-epidepride and the radiological response of NFPA to DA in 18 patients. Methods: Patients were treated with either cabergoline (1-2 mg/week) or quinagolide (150-30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…These results are in accordance with a previous report in which dopamine D2R imaging using [123] I-epidepride had limited clinical usefulness for predicting the efficacy of DA treatment in NFPA (22). Discordant studies reported the association of dopamine resistance in prolactinomas with low expression levels of the short (34) or long (35) isoforms of D2R.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in accordance with a previous report in which dopamine D2R imaging using [123] I-epidepride had limited clinical usefulness for predicting the efficacy of DA treatment in NFPA (22). Discordant studies reported the association of dopamine resistance in prolactinomas with low expression levels of the short (34) or long (35) isoforms of D2R.…”
Section: Discussionsupporting
confidence: 92%
“…Colao and coworkers (18) analyzed 24 studies published between 1981 and 2005, encompassing 199 patients, and report stabilization of over 90% of NFPA masses in patients treated with DA. Five studies (20,21,22,23,24) encompassing 54 patients used cabergoline (mean dose 1-3 mg/week) for the treatment of NFPA (primary treatment or postsurgical remnants) with mean follow-up times between 6 and 12 months. Pooled results indicate that tumor stabilization occurred in 85% of patients (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…123 I]epidepride D2R imaging showed the absence of correlation between the receptor-binding levels and the long-term efficacy of dopamine agonist treatments in terms of tumor mass stabilization or shrinkage (de Herder et al 2006). Consequently, we cannot provide an answer to the question why approximately one-third of the NFPA studied are insensitive to the chimeric compound.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, several studies have also shown a possible role for cabergoline in the treatment of non-functional pituitary adenomas. [22][23][24] In this issue of Cancer Biology & Therapy, Grossrubatscher et al show high expression of D 2 dopamine receptors in a large series of neuroendocrine tumors (NETs). 25 This study is the first in the literature to show the expression of D 2 receptors in a wide variety of human NETs, including the stomach.…”
Section: Commentarymentioning
confidence: 99%